A mensuração a valor justo dos ativos biológicos do setor de açúcar e álcool no Brasil: uma análise comparativa às companhias listadas na Bovespa - Gadducci, Vanessa Bargas Ferreira (2014)
Large contributions were incorporated into the national accounting scenario with the adaptation to international accounting standards, from then on, we could see in a more transparent way the organizational reality of the Brazilian companies. Brazil is a tropical country of great fertile land and the climatic factors contribute a lot to the large concentration of agricultural entities whose primary business is related directly to the land exploration by plantations. The agricultural sector has significant representation in the Brazilian economy moving 23% of the national GDP in 2013. In a country with natural vocation to explore business that engages biological assets with high diversification and full development, it becomes essential to deepening the methodology for valuation of these assets. By diversifying kind of cultivation and plantations cultivation in the country this study was limited to analysis the cultivation of sugar cane. Although the 6404 law from 1976 popularly known as the corporation law, have allowed the applicability of the method of valuation at fair value on stocks in general practice used in Brazil to record biological assets was the cost method and the constitution of stock agricultural products also gave the same methodology. Biological assets were measured at constitution cost without accounting incrementally recognition effects over natural mutations causing impact on the financial statements only when is sold. From the promulgation law 11,638 in 2011 that changed the corporation law, biological assets start to be evaluating by fair value. Due to the great complexity of the registration of the changes in biological assets, the goal of this study was to answer the following research issue: How to recognize and adequately measure the fair value of biological assets in companies that explore agricultural activities of sugar and alcohol ? The research began with a study over the conceptual framework of financial statements, deepened the particulars of accounting in the agricultural sector and extended analysis of the explanatory notes of biological assets of five companies listed on the stock exchange BOVESPA in the sugar and alcohol sector. The study concluded that although Brazil has advanced in the evaluation of biological assets with the application of fair value process, open companies explanatory notes were evasive on the explanation of fair value valuation and the obtaining of the discount rate used in projection of discounted cash flow